2007
DOI: 10.1124/jpet.107.123729
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Properties of 3-Amino-5,6,7,8-tetrahydro-2-{4-[4-(quinolin-2-yl)piperazin-1-yl]butyl}quinazolin-4(3H)-one (TZB-30878), a Novel Therapeutic Agent for Diarrhea-Predominant Irritable Bowel Syndrome (IBS) and Its Effects on an Experimental IBS Model

Abstract: 3-Amino-5,6,7,8-tetrahydro-2-{4-[4-(quinolin-2-yl)piperazin-1-yl]butyl}quinazolin-4(3H)-one (TZB-30878) is a novel compound with both 5-hydroxytryptamine (5-HT) 1A agonism and 5-HT 3 antagonism effects. We hypothesized that TZB-30878 might have benefits from these dual effects as a medication for diarrhea-predominant irritable bowel syndrome (d-IBS), and these studies were designed to confirm the pharmacological properties of TZB-30878 and its efficacy in an IBS-like animal model. The binding assays demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
25
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 33 publications
0
25
0
Order By: Relevance
“…They also exhibit modest agonist properties at 5-HT 1A receptors (Newman-Tancredi et al, 1998), so interpretation of their effects is complex. Any of these non-5-HT 2A actions could be responsible for the loss of antiparkinsonian (Lejeune et al, 1997); E max , 101% (Cornfield et al, 1991) Buspirone Reduces AIMs, impairs rotarod performance, this latter action may reflect loss of antiparkinsonian benefit (Dekundy et al, 2007) Reduces dyskinesia, but worsens parkinsonism (Ludwig et al, 1986;Bonifati et al, 1994) K i , 20 nM (Hamik et al, 1990); E max , 22% (Dupuis et al, 1999) Sarizotan Reduces AIMs (Marin et al, 2009) Reduces dyskinesia and L-DOPA antiparkinsonian benefit at high dose (Gregoire et al, 2009) Reduces dyskinesia (phase II) (Olanow et al, 2004), reduces dyskinesia compared with baseline, but not compared with placebo (phase III) (Goetz et al, 2008), no dyskinesia reduction and worsening of parkinsonism (phase III) (Goetz et al, 2007) K i , 2.2 nM (Newman-Tancredi et al, 2005); E max , 100% (Bartoszyk et al, 2004) Tandospirone Reduces dyskinesia, but worsens parkinsonism (Kannari et al, 2002) K i , 27 nM (Hamik et al, 1990); E max , 67% (Tamaoki et al, 2007) Anatomically Selective Therapies for Parkinson's Disease efficacy, and it could be argued that even the antidyskinetic actions of these compounds have little to do with 5-HT 2A antagonism. However, a PET study performed in schizophrenic patients demonstrated that at doses used to treat PD motor and nonmotor complications clozapine leads to greater 5-HT 2 than D 2 -like receptor occupancy (Nordström et al, 1995).…”
Section: -Ht 1a Agonist R-(ϩ)-8-oh-dpatmentioning
confidence: 99%
“…They also exhibit modest agonist properties at 5-HT 1A receptors (Newman-Tancredi et al, 1998), so interpretation of their effects is complex. Any of these non-5-HT 2A actions could be responsible for the loss of antiparkinsonian (Lejeune et al, 1997); E max , 101% (Cornfield et al, 1991) Buspirone Reduces AIMs, impairs rotarod performance, this latter action may reflect loss of antiparkinsonian benefit (Dekundy et al, 2007) Reduces dyskinesia, but worsens parkinsonism (Ludwig et al, 1986;Bonifati et al, 1994) K i , 20 nM (Hamik et al, 1990); E max , 22% (Dupuis et al, 1999) Sarizotan Reduces AIMs (Marin et al, 2009) Reduces dyskinesia and L-DOPA antiparkinsonian benefit at high dose (Gregoire et al, 2009) Reduces dyskinesia (phase II) (Olanow et al, 2004), reduces dyskinesia compared with baseline, but not compared with placebo (phase III) (Goetz et al, 2008), no dyskinesia reduction and worsening of parkinsonism (phase III) (Goetz et al, 2007) K i , 2.2 nM (Newman-Tancredi et al, 2005); E max , 100% (Bartoszyk et al, 2004) Tandospirone Reduces dyskinesia, but worsens parkinsonism (Kannari et al, 2002) K i , 27 nM (Hamik et al, 1990); E max , 67% (Tamaoki et al, 2007) Anatomically Selective Therapies for Parkinson's Disease efficacy, and it could be argued that even the antidyskinetic actions of these compounds have little to do with 5-HT 2A antagonism. However, a PET study performed in schizophrenic patients demonstrated that at doses used to treat PD motor and nonmotor complications clozapine leads to greater 5-HT 2 than D 2 -like receptor occupancy (Nordström et al, 1995).…”
Section: -Ht 1a Agonist R-(ϩ)-8-oh-dpatmentioning
confidence: 99%
“…2 Recently much attention has been devoted towards 4(3H)-quinazolinones derivatives due to their significant therapeutic and medicinal properties such as anti-inflammatory, 3 anti-convulsant, 4 anti-hypertensive, 5 antimalarial, 6 antiparkinsons activities 7 and they also show blood platelet anti-aggregating activity. 8 Therefore, several methods for synthesis of substituted 4(3H)-quinazolinones have been reported in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…11) Preliminary Studies to Find a Lead Compound Affinities of each compound binding to the 5-HT 1A receptor were calculated as percent inhibition (%) of binding of [ 3 H]-8-hydroxy-2-(di-n-propylamino)tetralin (8-OH-DPAT) (1) to the 5-HT 1A receptor in a CHO cell membrane sample in which human 5-HT 1A receptor was expressed. 13,14) Affinities of each compound binding to the 5-HT 3 receptor were calculated as percent inhibition (%) to binding of [ 3 H]BRL-43694 to the 5-HT 3 receptor in HEK-293 cell membrane sample in which human 5-HT 3 receptor was expressed. 13,14) We synthesized compounds using the pharmacophore model and performed a screening.…”
mentioning
confidence: 99%
“…13,14) Affinities of each compound binding to the 5-HT 3 receptor were calculated as percent inhibition (%) to binding of [ 3 H]BRL-43694 to the 5-HT 3 receptor in HEK-293 cell membrane sample in which human 5-HT 3 receptor was expressed. 13,14) We synthesized compounds using the pharmacophore model and performed a screening. Shown in Table 1, first, we synthesized compounds 7a and 7b, which fit in the pharmacophore model described above.…”
mentioning
confidence: 99%